Incorporating Artificial Neural Networks in the dynamic thermal–hydraulic model of a controlled cryogenic circuit. (September 2015) - Carli, S.; Bonifetto, R.; Savoldi, L.; Zanino, R.
Highlights: A simplified model of the heated line of HELIOS has been developed based on ANNs. The ANN is trained using 4C results to reproduce the dynamics of the heated line. The ANN model is tested against six operating scenarios with and without control. The ANN results are in good agreement with full 4C and experimental data. Abstract: A model based on Artificial Neural Networks (ANNs) is developed for the heated line portion of a cryogenic circuit, where supercritical helium (SHe) flows and that also includes a cold circulator, valves, pipes/cryolines and heat exchangers between the main loop and a saturated liquid helium (LHe) bath. The heated line mimics the heat load coming from the superconducting magnets to their cryogenic cooling circuits during the operation of a tokamak fusion reactor. An ANN is trained, using the output from simulations of the circuit performed with the 4C thermal–hydraulic (TH) code, to reproduce the dynamic behavior of the heated line, including for the first time also scenarios where different types of controls act on the circuit. The ANN is then implemented in the 4C circuit model as a new component, which substitutes the original 4C heated line model. For different operational scenarios and control strategies, a good agreement is shown between the simplified ANN model results and the original 4C results, as well as with experimental data from the HELIOS facility confirming the suitability of this new approach which, extended to an entire magnet systems, can lead to real-time control of the cooling loops and fast assessment of control strategies for heat load smoothing to the cryoplant.